2020
DOI: 10.1136/jitc-2020-000742
|View full text |Cite
|
Sign up to set email alerts
|

Continuous renal replacement therapy in cytokine release syndrome following immunotherapy or cellular therapies?

Abstract: Recently, an increasing number of novel drugs were approved in oncology and hematology. Nevertheless, pharmacology progress comes with a variety of side effects, of which cytokine release syndrome (CRS) is a potential complication of some immunotherapies that can lead to multiorgan failure if not diagnosed and treated accordingly. CRS generally occurs with therapies that lead to highly activated T cells, like chimeric antigen receptor T cells or in the case of bispecific T-cell engaging antibodies. This, in tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 66 publications
0
24
0
Order By: Relevance
“…This study has demonstrated that CRRT is effective in mitigating sepsis which has a similar pathophysiological mechanism to CRS (111). However, as such studies themselves indicate that there are still various unanswered questions in this field that require addressing (111).…”
Section: Hemofiltrationmentioning
confidence: 75%
See 2 more Smart Citations
“…This study has demonstrated that CRRT is effective in mitigating sepsis which has a similar pathophysiological mechanism to CRS (111). However, as such studies themselves indicate that there are still various unanswered questions in this field that require addressing (111).…”
Section: Hemofiltrationmentioning
confidence: 75%
“…It is important to state that in this case, tocilizumab and glucocorticoids were not successful in controlling the mentioned adverse events (110). Furthermore, another study has also proposed that continuous renal replacement therapy (CRRT) can be an additional approach for controlling CAR-T therapy-related CRS that is resistant to conventional treatment (111). This study has demonstrated that CRRT is effective in mitigating sepsis which has a similar pathophysiological mechanism to CRS (111).…”
Section: Hemofiltrationmentioning
confidence: 92%
See 1 more Smart Citation
“…Using CRRT for immunomodulation has a long history in clinic for tapering cytokine storms and controlling the associated dysregulation of the immune system. This approach has also been proposed as adjuvant therapy in many diseases, including sepsis (22), septic AKI (35), septic shock (32), severe Middle East Respiratory Syndrome (MERS) (5), severe acute pancreatitis (SAP) with or without ARDS (9,11), CRS induced by some immunotherapies (7), severe burns (27), etc. Yet, a non-selective way allows harmful and bene cial substances to be simultaneously removed during CRRT (33).…”
Section: Discussionmentioning
confidence: 99%
“…These are T-cells that are engineered to present a receptor for a specific antigen that, when encountering the antigen, activate the engineered T-cell. A common effect among this class of therapeutics is cytokine release syndrome (CRS) that occurs between 60% and 80% of treated patients [ 38 , 39 , 40 , 41 ]. CRS is characterized by a massive release of inflammatory cytokines and subsequent multiorgan dysfunction.…”
Section: Car-t Cells and Bispecific Antibodiesmentioning
confidence: 99%